Application of Du-moxibustion in patients with cerebral infarction of Qi deficiency and blood stasis syndrome in the convalescent stage (督灸在脑梗死恢复期气虚血瘀证患者护理中的应用) - LI Silu (李思璐); LUO Lihua (罗丽华); YANG Yanni (杨燕妮); CHEN Lu (陈璐); GENG Qingwen (耿庆文) (中西医结合护理)
As a common type of Traditional Chinese Medicine nursing technique, Du-moxibustion has the advantages of easy-to-operate, convenient, low cost, efficient and healthy, and is effective in clinical nursing practice of cerebral infarction. This paper reviewed studies on pathogenesis, theoretical studies and clinical practice of Du-moxibustion therapy in the treatment of cerebral infarction of Qi deficiency and blood stasis syndrome, and provided reference for the improvement of quality of nursing. (督灸作为常用的中医适宜技术之一, 具有简、便、廉、验的优势, 在脑梗死的临床护理中效果明确。本文从脑梗死恢复期气虚血瘀证病机、督灸治疗脑梗死恢复期气虚血瘀证的理论研究及护理临床应用方面进行综述, 为提升护理效果提供参考。)